The Effect of Using NISP Strategy on Students' Achhievement in Reading Comprehension of the Tenth Grade of SMA GKPI Medan - Priska Dinda Situmorang (JETAL: Journal of English Teaching & Applied Linguistic, 2019)
The objective of this study is to investigate the influence of NISP strategy on students’ achievement in reading comprehension. The population was all of the tenth grade students of SMA GKPI Medan. The sample was the students of X-IPS 2 (experimental) and X-IPS 1 (control). This study used experimental design. The mean score of pre-test in experimental class was 64 and the post-test was 81,53. The mean score of pre-test in control group was 51,26 and the post-test was73,53. Moreover, the analysis of t-test showed that tscore > ttable or 3,01 > 1,672 at the level of significance 0,05 with the degree of freedom (df) 58. It is clear that the alternative hypothesis (Ha) is accepted. It means that NISP strategy is effective media in teaching reading narrative text.